Volatile outcomes of essential public health functions: a cross-sectional study of surveillance and equitable access on Brazil’s Unified Health System (SUS) - Jatobá, Alessandro; Castro-Nunes, Paula; Carvalho, Paulo Victor Rodrigues de (Frontiers in Public Health, 2025)
BackgroundThis study investigates the volatility in the outcomes of Essential Public Health Functions (EPHFs) and elaborates on its potential impacts on the operation of Brazil’s Unified Health System (SUS). The research addresses the need to understand how performance variability in EPHFs affects health system stability, particularly during external shocks such as the COVID-19 pandemic, and its potential effects on the system’s resilience.MethodsUsing cross-sectional data (2000–2023) from the Department of Informatics of the SUS (DATASUS), the study analyzes key indicators linked to two EPHFs: (1) Surveillance, control, and risk management (infant mortality) and (2) Equitable access to comprehensive and quality services (cytopathological tests and mammography screenings). Volatility was defined as deviations from central trends exceeding one standard deviation relative to prior years. These metrics were assessed to evaluate health system performance and resilience.ResultsSignificant volatility was observed across indicators, particularly during the COVID-19 pandemic, which disrupted service levels and exposed systemic vulnerabilities. Infant mortality declined by 60% since 2000 but exhibited persistent fluctuations. Cytopathological tests and mammography screenings saw sharp declines during the pandemic, reflecting systemic challenges in sustaining equitable access to care.ConclusionThe study proposes a conceptual framework to analyze EPHF performance through a resilience lens, emphasizing the need to manage variability for stable, high-quality service delivery in the SUS. Recommendations include strengthening health data systems, integrating contextual factors into resilience planning, and enhancing institutional capacity. This work advances efforts to operationalize resilience assessments in universal health systems, offering actionable insights for policymakers and practitioners.